Enhancing Georgetown’s Heritage Boutique Hotel Marketing Strategies: The Case Of 1881 Chong Tian Cultural Hotel - Mahmood, Amalina; Venugopal, Malini; Roslan, Naj Rizal (2014)
1881 Chong Tian Cultural Hotel business is identified to be running in loss since it’s establishment; loss about USD53.7k in year 2011. The business issue needs to be addressed in order to reduce the losses before it become worsen and impacts the business as overall. Based on the research done, the main root causes are due to poor cultural service quality and poor marketing strategies. The hotel had failed to reflect the uniqueness of the heritage and cultural values in its service delivery in terms of the hotel’s ambience, cultural service and cultural infrastructure.